Virtual Assistant for the Registration of Clinical Histories Using Natural Language Processing in the Health Sector - Campos, Alexis (2024)
Medicine has evolved over time, utilizing technology to automate its relevant processes and expedite healthcare delivery. A notable example is electronic medical records, which would facilitate a doctor’s task when recording them, as it often becomes cumbersome and involves wasted time. However, many healthcare specialists with a higher age demographic find it challenging to adapt to digital or virtual environments for the completion of these medical records, which would streamline their documentation. Therefore, the focus of this present study is on a virtual assistant that, employing natural language processing, will serve the purpose of resolving the described problem, all through voice commands. The system was validated through a testing scenario with a sample of thirty users, using a success indicator that measures the percentage reduction in the time required to complete a medical history. Consequently, an average reduction of 54.1% in the time required for medical history recording was achieved. Additionally, 70% of the participants perceived that the virtual assistant would contribute to the optimization of medical history recording. Likewise, 80% considered the user interface to be pleasant and intuitive.